Heterotic parametrization for economically important traits in popcorn - DOI: 10.4025/actasciagron.v31i3.4689 - Vieira, Rafael Augusto; Souza Neto, Israel Leite; Bignotto, Lucas Souto; Cruz, Cosme Damião; Amaral Júnior, Antonio Teixeira do; Scapim, Carlos Alberto (Acta Scientiarum. Agronomy, 2009)
Six popcorn varieties were crossed in a diallel mating scheme to obtain 15 F1 hybrids, with the purpose of analyzing the estimates of heterotic parametrization for agronomically important traits. The genitors and hybrids were evaluated in randomized block design with three replications in Viçosa and Visconde do Rio Branco, in Minas Gerais State, Brazil, in three growing seasons. Six traits were evaluated, including grain yield and popping expansion. There were highly significant effects for treatments, varieties and mean heterosis for plant and ear heights, and for the others traits the significance extended to all sources of variation. Amarela and Viçosa revealed superiority for grain yield in relation to performance per se, while Rosa Claro expressed the highest effect of varietal heterosis. The best combinations for grain yield were Roxa x Viçosa, Amarela x Rosa Claro, Rosa Claro x Beija-Flor and Branca x Beija-Flor. For popping expansion, there were positive and negative values for specific heterosis in all growing seasons evaluated, ratifying the influence of bidirectional dominance on this trait. Simultaneous genetic gains for grain yield and popping expansion may be obtained by using Viçosa in intrapopulational programs, while Amarela and Rosa Claro are recommended for using in interpopulational breeding.